Equivalent circuit characterization of a parallel‐wire T‐junction discontinuity with radiation loss. Issue 6 (30th March 2017) - Choi, Dooseok; Hong, Wonbin; Park, Wee Sang
ABSTRACT: We investigate the radiation loss principle of a parallel‐wire T‐junction and present a novel equivalent circuit representation at the 60‐GHz band. Discontinuities introduced at right‐angle bends within the T‐junction structure induce time varying magnetic fields which generate radiating leakage in the form of Poynting vectors. We devise and demonstrate an equivalent circuit which can accurately speculate the radiation leakage through the additional modeling consisting of four discrete and frequency‐dependent resistors. The presented model can be used in conjunction with the conventional T‐junction equivalent circuit model which consists of three inductors and one capacitor. The resistors are calculated based on the scattering parameters, which is retrieved using finite‐element numerical analysis. The proposed equivalent circuit is ascertained to exhibit less than 0.6 dB deviations in radiation leakage between the equivalent circuit representation and simulated results. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1434–1438, 2017